2006
DOI: 10.1113/jphysiol.2005.101600
|View full text |Cite
|
Sign up to set email alerts
|

Length‐dependent changes in voluntary activation, maximum voluntary torque and twitch responses after eccentric damage in humans

Abstract: To assess the contribution of central and peripheral factors to changes in maximum voluntary force and its length dependence after eccentric muscle damage, voluntary and twitch torque were measured across a wide angular range, along with voluntary activation using twitch interpolation. Isometric torque from both maximum voluntary contractions (MVCs) and paired twitches to motor nerve stimulation were measured from 60 to 150 deg elbow flexion in 10 deg increments in eight subjects. Optimal angles were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
6
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 53 publications
(78 reference statements)
12
95
6
9
Order By: Relevance
“…28,29 Concurrent PNS and TMS measurements of VA can be used to dissociate supraspinal fatigue from central fatigue of other origins. 8,18,21,22,25,27 Although previous studies have found a close agreement in the measurement of VA with both PNS and TMS, 4,28 there are methodological issues that complicate direct comparison between the two methods. For example, VA measured with TMS has a direct linear relationship with force, whereas VA measured with PNS is curvilinear at high contraction strengths.…”
Section: Accepted 18 April 2008mentioning
confidence: 96%
“…28,29 Concurrent PNS and TMS measurements of VA can be used to dissociate supraspinal fatigue from central fatigue of other origins. 8,18,21,22,25,27 Although previous studies have found a close agreement in the measurement of VA with both PNS and TMS, 4,28 there are methodological issues that complicate direct comparison between the two methods. For example, VA measured with TMS has a direct linear relationship with force, whereas VA measured with PNS is curvilinear at high contraction strengths.…”
Section: Accepted 18 April 2008mentioning
confidence: 96%
“…This protocol was used to obtain similar muscle damage in all subjects, compared with the large variation in strength loss between subjects following a set number of eccentric contractions (Hubal et al 2007). Furthermore, this eccentric exercise protocol has been shown to produce consistent changes in elbow flexors indicative of muscle damage, which include a shift in optimal muscle length, a reduction in relaxed elbow joint angle (increased passive tension), and DOMS for several days following the exercise (Prasartwuth et al 2005(Prasartwuth et al , 2006. The subject was seated at a bench that consisted of an adjustable height seat and a padded support for the left (nondominant) upper arm that was positioned 45°from the torso.…”
Section: Eccentric Exercisementioning
confidence: 99%
“…DOMS usually appears 24 hours after the exercise, with peak of pain between 48 to 72 hours after the exercise 17,18 . During the period of pain, the individual may present restriction of range of movement and deficit of maximum muscle strength 19,20 . Exercise Therapy has been a physiotherapeutic intervention recommended by clinical practice directives to improve symptoms of patients with musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%